Pilvimigraatioprosessin vakiointi organisaatiossa: suunnittelutieteellinen tutkimus - Hulsi, Sara (2025)
Cloud services have been part of technological development for a long time now. Organizations in different industries have migrated their information systems and their infrastructures into cloud-based platforms to remain competitive. Organizations try to increase their performance and environments with cloud migration projects. Such projects can be challenging and may fail, and the consequences can be serious for the business. A successful cloud migration project requires for experienced project managers with the right tools for minimizing the risks. For responding to this demand, this master’s thesis aims to investigate what types of cloud migration process models exists and to design a standardized cloud migration process for an organization and study changes that might occur. A literature review is conducted in this thesis. The review investigates cloud migration process models, their stages and features, that are used for managing the migration process and risks. In the empirical part of this thesis is design science research where an artefact, a standardized cloud migration process is created. Impacts of the process for the project are studied by using interview method. As outcome of this study is that the standardized cloud migration process changed project management aspects of the projects such as human resources, scheduling and costs. All these aspects influenced risk management, as the risks diminished. This research establishes the risk management aspect of cloud migration processes in the literature. The standardized cloud migration process can be exploited by the organization and further develop. With the development of artificial intelligence, the need for cloud migrations will continue its current growing trend.